Extraction and Stability of Anthocyanins From Jambolan (SYZYGIUM CUMINI) Skins - PuspitaSari .; Fitria Agustina; Mukhamad Komar; Unus .; Mukhamad Fauzi; Triana Lindriati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
Anthocyanins were extracted from jambolan skins using neutral solvents e.i water, ethanol, sopropanol, water ; ethanol (1:1), water : isopropanol (1:1), ethanol : isopropanol (1:1), and water, ethanol, isoppropanol (1:1:1) at 5 and 270>C. the stability of the anthocyanins was as effected by pH, heat, oxidator, and light was investigated. The extraction using combination of water and isopropanol at 270C showed the highest total yield, i.e 71.54% (db). Furthermore, the highest anthocyanin concentration and yield were obtained in the extracts using combination of water and ethanol at 270>C i.e. 10 007.03 mg/L (db) and 2.78% (db), respectively. At low pH, the pigment extracts sowed high stability; and gradually decreased and lost color when the pH was increased. The greatest color intensity (red) was obtained at pHs values less than 3.5. The anthocyanins were relatively stable during heating temperature of 40 and 600C in which more than 80% of pigment could be maintained for 4 hour of heating. Heating at high temperatures (80 and 1000C) decreased the color stability more than 80%. Presence of oxidator H2O2 reduced the stability up to 73.52%. The UV and flouresecent light exposure for 7 days also reduced the stability by 11.47% and 10.62%, respectively. Key words: Anthocyanins, Jambolan skin, Extraction, pigment stability